2022
DOI: 10.1002/adma.202200354
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Thermodynamic and Kinetic Contributions to the Stability of Doped Nanocrystalline Alloys using Nanometallic Multilayers

Abstract: Targeted doping of grain boundaries is widely pursued as a pathway for combating thermal instabilities in nanocrystalline metals. However, certain dopants predicted to produce grain‐boundary‐segregated nanocrystalline configurations instead form small nanoprecipitates at elevated temperatures that act to kinetically inhibit grain growth. Here, thermodynamic modeling is implemented to select the Mo–Au system for exploring the interplay between thermodynamic and kinetic contributions to nanostructure stability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…[40][41] Therefore, inhibiting grain growth during the sintering process for nanostructured TE materials could provide much-needed thrust in the wide-scale application of TE technology. The propensity of grain growth depends on the GB velocity (v), as described by [42]…”
Section: Introductionmentioning
confidence: 99%
“…[40][41] Therefore, inhibiting grain growth during the sintering process for nanostructured TE materials could provide much-needed thrust in the wide-scale application of TE technology. The propensity of grain growth depends on the GB velocity (v), as described by [42]…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that the main driving force is the inhomogeneous elastic strain energy caused by a mismatch in thermal expansion between the metallic phase of the metamaterial and the substrate. This contribution has often been disregarded [39,47] or assumed to be homogeneous. [38] Notably, the observed instability is tightly related to the HMM design, as co-sputtered Ag/a-Si [55] thin films preserve their structural integrity in the studied temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the anisotropic elastic strain energy due to thermal expansion mismatch is identified as the predominant driving force. Most previous literature on multilayer instabilities disregards this effect and treats the morphological redistribution in the context of interfacial energy minimization, including work on sputtered Ag/a-Si multilayers, [44,45] other systems with high CTE missmatch, [46][47][48] predictive models, [39,49] and reviews. [50] It should be noted that these conclusions are often based on experiments using transmission electron microscopy (TEM).…”
Section: Thermodynamics Of the Instabilitymentioning
confidence: 99%
“…While several studies demonstrated thermally stable NC materials through alloying and subsequent GB segregation, absent from such studies is a detailed understanding of the role of TJ solute segregation in the evolution of nanostructures and stability of NC alloys. In addition to GBs, dislocations, and point-defects, TJs are an important part of the repertoire of defects in crystalline solids.…”
mentioning
confidence: 99%